A note on cetaceans off Kiribati and Tuvalu from a research cruise in October 2010 - Murase, Hiroto; Temoai, Ioneba; Kirata, Taratau; Finkaso, Samasoni; Yasunaga, Genta; Pastene, Luis A. (J. Cetacean Res. Manage., 2023)
This paper summarises the results of a sighting survey conducted around the Gilbert Islands (Kiribati) and Tuvalu Islands (Tuvalu) in the central Pacific Ocean between 3 and 17 October 2010. This was the first systematic collection of cetacean sighting data in this region. The main objective of the survey was to investigate the occurrence and distribution of cetaceans around Kiribati and Tuvalu. In addition biopsy samples were obtained to investigate the species identity of Bryde’s-whale-like baleen whales through genetic analyses and to assess feeding ecology of cetaceans in the survey area through the examination of fatty acids. The survey was carried out using a sighting survey vessel, which covered a total of 1,012 n.miles (≈1,875km). A total of 24 schools (640 individuals) of cetaceans was sighted: three schools (five individuals) of Bryde’s-whale-like baleen whales, one school (nine individuals) of sperm whales (Physeter macrocephalus), one school (six individuals) of killer whales (Orcinus orca), one school (14 individuals) of short finned pilot whales (Globicephala macrorhynchus), one school (two individuals) of false killer whales (Pseudorca crassidens), eight schools (483 individuals) of spinner dolphins (Stenella longirostris), and one school (70 individuals) of striped dolphins (Stenella coeruleoalba). Mitochondrial DNA (mtDNA) analyses based on the biopsy samples identified two of the Bryde’s-whale-like whales sighted, as of the putative species Balaenoptera brydei. Compositions of fatty acids of Bryde’s and killer whales are presented. The survey provided new information on the distribution and fatty-acid composition of cetaceans around Kiribati and Tuvalu.